Modern methods of stimulation of angiogenesis in patients with critical limb ischemia (review) - Kryvoruchko, I. A.; Goni, S. K.-T.; Antonova, M. S.; Sykal, M. A.; Voronaja, U. M.; Alexandrov, M. A.; Lola, N. V. (Journal of Education, Health and Sport, 2017)
The term "critical ischemia of extremities" (critical limb ischemia) was first introduced by P.R.F. Bell in 1982 to refer to a group of diseases accompanied by pain in the legs at rest, trophic ulcers and distal necroses of the lower limbs. Critical ischemia of the lower limbs is a condition of almost complete cessation of arterial blood flow to the tissues of the lower limbs. If the arterial blood supply is not improved, limb amputation becomes inevitable for all patients. Treatment of ischemia of the lower extremities should be complex and differentiated depending on the stage and features of the course of the disease. Modern approaches to the therapy of lower limb ischemia include conservative and surgical methods of treatment, all of which are aimed at improving blood flow in the affected limbs. In the article modern methods of stimulating angiogenesis in patients with lower limb ischemia and results are shown.